Detection of Wolbachia Endosymbiont in Several Agriculturally Important Insect Parasitoids in Bogor, Indonesia - Mahardika Gama Pradana; Giyanto Giyanto; Seiichi Furukawa; Satoshi Nakamura; Damayanti Buchori (AGRIVITA, Journal of Agricultural Science, 2019)
Wolbachia that have been found to be maternally inherited in arthropods, including insects behave primarily as a reproductive parasite by inducing feminization and/or death among genetic males; causing cytoplasmic incompatibility, and activating parthenogenesis, in host insects. This research aims to detect the presence of Wolbachia in several parasitic insects and to determine the diversity of Wolbachia at the supergroup level. Insect genetic samples were collected, amplified using wsp (Wolbachia surface protein) gene and with the sequences then analyzed using species homologues drawn from the Genbank database. These activities were dedicated to detect intracellular presence of Wolbachia and assembled the phylogenetic tree of the respected bacteria. Phylogenetic analysis confirmed that Wolbachia existed in the samples belonged to the supergroup A (found in Cherapron sp.) and supergroup B (found in E. japonica). Wolbachia were detected in seven out of nine wasps i.e. Anagyrus lopezi, Ceraphron sp., Microplitis manilae, Brachymeria lasus, Scelionidae sp01, Trichogramma sp, and Exorista japonica. Single infection by Wolbachia supergroup A was detected in A. lopezi, Ceraphron sp., M. manilae, and Scelionidae sp01. Meanwhile single infection by Wolbachia supergroup B was detected only in E. japonica. Double infection by both supergroups occurred in B. lasus and Trichogramma sp. samples.